2011
DOI: 10.1097/aog.0b013e3182319737
|View full text |Cite
|
Sign up to set email alerts
|

Planned Home Compared With Planned Hospital Births in The Netherlands

Abstract: Home birth, under routine conditions, is generally not associated with increased intrapartum and early neonatal death, yet in subgroups, additional risk cannot be excluded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 82 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…For example, the Dutch home-birth system (in which home birth is common and adverse outcomes are rare) includes formal collaborative agreements between out-of-hospital and in-hospital providers, clear and mutually agreed-upon stratification of risk, and protocols for the transfer of care. 35,36 The process of devising evidence-based guidelines for U.S. home births is under way. 37 …”
Section: Discussionmentioning
confidence: 99%
“…For example, the Dutch home-birth system (in which home birth is common and adverse outcomes are rare) includes formal collaborative agreements between out-of-hospital and in-hospital providers, clear and mutually agreed-upon stratification of risk, and protocols for the transfer of care. 35,36 The process of devising evidence-based guidelines for U.S. home births is under way. 37 …”
Section: Discussionmentioning
confidence: 99%
“…These studies have found births at home and at birthing centers to have lower obstetrical resource use with associated decreases in maternal complications of interventions such as operative vaginal delivery, cesarean delivery, episiotomy, and epidural use. 4,18,2025,29 Several studies have found that home births increase the risk of adverse neonatal outcomes, 4,11,19,24,2830 although some have concluded there are no increased risks of adverse perinatal or maternal outcomes. 18,20,26,27 Studies of planned home births compared to planned hospital births involve a mixing of the level of care available at home and the characteristics of women who self-select for home births that make results difficult to interpret.…”
Section: Commentmentioning
confidence: 99%
“…The use of planned rather than actual place of delivery is justified by the assumption that there is less endogeneity in planned than in actual birth place, since the actual birth place may deviate from the planned one due to changes in individual health and risk factors. The results, interpreted as an intention-totreat effect, are mixed, with some studies showing higher perinatal mortality risk among home births (e.g., Bastian et al, 1998;Pang et al, 2002;Kennare et al, 2010;Malloy, 2010;Birthplace in England Collaborative Group, 2011) and others finding no significant differences (e.g., Ackermann-Liebrich et al, 1996;Murphy and Fullerton, 1998;Janssen et al, 2002;Lindgren et al, 2008;de Jonge et al, 2009;van der Kooy et al, 2011).…”
Section: Previous Literaturementioning
confidence: 99%